Raman spectroscopy in nanomedicine: current status and future perspective. (August 2013) - Keating, Mark E; Byrne, Hugh J
Raman spectroscopy is a branch of vibration spectroscopy that is capable of probing the chemical composition of materials. Recent advances in Raman microscopy have significantly added to the range of applications, which now extend from medical diagnostics to exploring the interfaces between biological organisms and nanomaterials. In this review, Raman is introduced in a general context, highlighting some of the areas in which the technique has been successful in the past, as well as some of the potential benefits it offers over other analytical modalities. The subset of Raman techniques that specifically probe the nanoscale, namely surface- and tip-enhanced Raman spectroscopy, will be described and specific applications relevant to nanomedical applications will be reviewed. Progress in the use of traditional label-free Raman for investigation of nanoscale interactions will be described, and recent developments in coherent anti-Stokes Raman scattering will be explored, particularly its applications to biomedical and nanomedical fields.